PSYCHOSOCIAL TUTOR INTERVENTIONS TO REDUCE LONELINESS AND PSYCHOLOGICAL DISTRESS AMONG OPEN UNIVERSITY STUDENTS - A Hadian Pratama Hamzah; Zamroni; Abdurrohim; Agustin Handayani; Joko Koncoro (World Psychology, 2026)
This study aims to examine the challenges faced by distance education students, particularly loneliness and difficulties in social adaptation due to limited interpersonal interaction. It also seeks to identify strategies that can reduce psychological distress and improve students’ adaptation and participation in the distance learning environment. The study applies a narrative literature review approach. Data collection began with formulating research questions, followed by searching for relevant academic journals through electronic databases and credible reference sources. To strengthen the analysis, additional insights were obtained through interviews with groups of students from several open universities. The findings show that distance education students are vulnerable to loneliness, social maladaptation, and reduced learning performance due to limited interaction with peers and instructors. Difficulties in forming study groups and the absence of direct communication contribute to psychological and academic challenges. The study also finds a strong relationship between psychosocial support and reduced loneliness. Higher levels of social support from tutors and academic staff are associated with lower levels of loneliness and better student adaptation to the distance learning environment. The novelty of this research lies in emphasizing tutor-mediated psychosocial support as an integrated strategy to address loneliness and social maladaptation among distance learning students within the framework of open and distance education. The study implies that open universities should strengthen institutional support systems by integrating psychosocial assistance from tutors and academic officers into learning services to enhance student well-being, improve adaptation to distance learning culture, and increase academic success.